(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article analyzes the differences between two versions of the “Payback” movie, the causes of these differences and their impact on the dramaturgy of the film, as well as on the characteristics of the genre. Article describes the situation which leads to the creation of two different versions. Article explains how film characters were formed, why they need to be changed, and how they affect the viewer perception of the film as a whole. Article analyzes director’s techniques with which the characters have been changed, analyzes how changes to film edit were made. Article explains the necessity to create a different ending, the internal architecture of both endings, the differences between negative characters in different versions. Results of the analysis are summarized for film art in general. Key words: film, editing, dramaturgy, payback, the story, the character.